Intention to COVID-19 vaccination and associated factors among health care workers: A systematic review and meta-analysis of cross-sectional studies - Luo, Chuxuan; Yang, Yuan; Liu, Yueming; Zheng, Danna; Shao, Lina; Jin, Juan; He, Qiang (American journal of infection control, 2021)
•COVID-19 vaccination acceptance of health care workers (HCWs) was at moderate level.•Male HCWs, aged 30 years or older, with a history of prior influenza vaccination were more likely to get vaccinated against COVID-19.•No other meta-analysis has yet investigated intention to COVID-19 vaccination and associated factors among HCWs. To gain insight into willingness and its influencing factors to vaccinate against COVID-19 among health care workers (HCWs), and provide a scientific basis for more reasonable epidemic prevention and control strategies. A comprehensive literature search was conducted in 4 English databases (PubMed, EMBASE, Web of Science and the Cochrane Library) and 4 Chinese databases (Chinese National Knowledge Infrastructure (CNKI), the Chongqing VIP Chinese Science (VIP), Wanfang Database and China Biomedical Literature Database (CBM)) to collect the related studies. Quality evaluation was carried out for papers meeting the inclusion criteria using 6 items from the Downs and Black assessment checklist. The STATA statistical software version 15.1 was hired to perform meta-analysis. Nine records with a total of 24,952 subjects were included in this meta-analysis. The results of this meta-analysis revealed that the pooled effect value of COVID-19 vaccination willingness among HCWs using a random-effects model was 51% (95% confidence interval (CI) 0.41-0.62). Male, aged 30 years or older, having a history of prior influenza vaccination were facilitators for HCWs’ intention to vaccinate against COVID-19 (odds ratio (OR) 1.82, 95% CI 1.37-2.41, P = .000, I2 = 59.4%; OR 1.32, 95% CI 1.16-1.51, P = .000, I2 = 31.7%; OR 2.97, 95% CI 1.82-4.84, P = .000, I2 = 88.1%). The impact of occupation on HCWs’ intention to get vaccinated could not yet be definitively confirmed (OR 0.85, 95% CI 0.69-1.06, P = .160, I2 = 85.5%). COVID-19 vaccination acceptance of HCWs was at moderate level. Strengthening awareness of COVID-19 vaccine among HCWs, particularly female HCWs under 30 years who have no history of prior influenza vaccination, is crucial to eliminate concerns about vaccination and promote the application of COVID-19 vaccine in this population.